Marketing Strategy Based On Event Marketing And Sponsorship To Increase The Number Of Cimory Milk Product Customers - Sitorus, Petra Herlan; Nurzam, Nurzam; Putra, Iswidana Utama (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2025)
The aim of this research is to determine which marketing strategies based on event marketing and sponsorship can increase the number of customers for Cimory Milk products. This type of research is quantitative. The data collection method in this research used a questionnaire technique, with a sample of 100 respondents. The results of the research show that the multiple linear regression Y = 26,889 + 0.332 increase the number of customers for Cimory dairy products. The results of the event marketing test (XI) show tcount 5.336 > ttable 1.984 and significance 0.000 < 0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning that event marketing has a positive and significant effect on increasing the number of customers for Cimory milk products. The results of the sponsorship test (X2) show tcount 5.336 > ttable 1.984 and significance 0.045 <0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning that event marketing has a positive and significant effect on increasing the number of customers for Cimory milk products. Based on the comparison of the Fcount value with Ftable, the Fcount value is greater than the Ftable value, namely 17.314 > 2.70, so it is concluded that accepting the hypothesis, this means that there is a simultaneous influence between event marketing (XI) sponsorship (X2) to increase the number of customers for Cimory milk products. This can be seen at the significance level of 0.000 <0.05.